SISTEM MANAGEMEN KEUANGAN KOPERASI AT-TARBIYAH STAIN PAREPARE - RUSNAENA, RUSNAENA; AMIN, ST. JAMILAH; DAMIRAH, DAMIRAH (P3M STAIN Parepare, 2014)
This article discusses the Cooperative Financial Management System At-MT STAIN Pare Pare, where the main focus of study to see if the cooperative at-MT attention to the welfare of its members and adhered to the establishment of cooperative goals are: to help improve the welfare of its members, not to maximize proft cooperative enterprise. Initial observations the authors see that cooperative At-MT STAIN Pare Pare very helpful members. On the other hand, criticism and complaints from sebahagian members, as well as distrust in terms of capital and profts in the can through the division of SHU annually. This research is a feld research, data sources used in this study are: primary data, secondary data, and fnancial management of the cooperative.This study uses data collection techniques: (1). Observation, (2). Interviews, and (3). Document. To analyze the data that has been collected, the data is processed by qualitative analysis techniques.The results of this study indicate that: 1. Systems cooperative capital STAIN Pare Pare At-MT consists of principal, save mandatory and voluntary savings of the members of the cooperative. 2. The fnancial performance of cooperative inadequate and has not been managed well seen by the presence of some of the bad loans that have not been resolved by the cooperative management STAIN Pare Pare. 3. The health cooperative AT-MT STAIN Pare Pare is still very far from the standard assessment when returning to the assessment ratio cooperative fnancial services cooperatives (KJK) both in terms of capital, asset quality, proftability, and the quantifcation of management aspects.